New species and record of xanthid crabs (Crustacean, Decapoda) from Taiwan - Hsueh, Pan-Wen (Zootaxa, 2020)
A new species and a new record species of xanthid crabs collected from shallow subtidal hard bottoms of Taiwanese waters are described in the present study. Garthasia ludaoensis n. sp. represents the second species for the genus and can be readily distinguished from the type species, G. americana (Garth, 1939), by having: 1) smaller width to length ratio of the carapace; 2) larger width to length ratio of the third maxilliped; 3) smaller width to length ratio of merus of the third maxilliped; 4) no distinct longitudinal keel on surfaces of sternites 1 and 2; 5) smaller length to width ratio of merus of the last ambulatory leg; 6) smaller width to length ratio of pleonite 2 of the male abdomen; 7) pleonite 2 in semicircular-shaped; 8) a tuft of long setae near distal opening of G1; and 9) distal end of basal segment without upright protrusion of G2. This genus is reported for the first time from Taiwan, as well as from the West Pacific. The second xanthid crab specimen examined in the present study has live colour pattern of the carapace and morphological characters similar to that of Zosimus maculatus (de Man, 1887) described from Ambon, Indonesia (about 3.7° S). The present finding extends the northern distribution range of this species to near 22° N and represents a new record of this species for Taiwan.